2020
DOI: 10.15376/biores.15.4.8303-8322
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ball-milled bamboo-based activated carbon treated with KMnO4 and KOH as activating agents

Abstract: Bamboo-based activated carbon was made using the activating agents KOH and KMnO4 at high temperature. This study examined the ability of unmilled and ball-milled bamboo activated using KOH or KMnO4 to fulfil the activated carbon standard parameters. Chemical activation was done using KOH and KMnO4 at 2.5% and 5% concentration, heated at 800 °C, and steamed for 1 hour. Sample size was reduced to 500 nm using high energy ball-milling at 500 rpm for 80, 150, or 180 min. Analysis included the yield, water content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…5(b) shows more pronounced particles' deformation at 30 h of milling times, changing the sample morphology due to the shear force applied by the metallic balls on the surface of biochar particles in the mono planetary stainless-steel jar. This result followed other researchers who showed significant particle size reduction after periods of ball milling (Phanthong et al 2018;Lyu et al 2018;Qanytah et al 2020). However, the particle size remained constant after 30 h of milling, as no further changes were observed.…”
Section: Morphological and Porosity Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…5(b) shows more pronounced particles' deformation at 30 h of milling times, changing the sample morphology due to the shear force applied by the metallic balls on the surface of biochar particles in the mono planetary stainless-steel jar. This result followed other researchers who showed significant particle size reduction after periods of ball milling (Phanthong et al 2018;Lyu et al 2018;Qanytah et al 2020). However, the particle size remained constant after 30 h of milling, as no further changes were observed.…”
Section: Morphological and Porosity Propertiessupporting
confidence: 90%
“…The result was similar to findings by Shan et al (2016), who reported that coconut shell-based activated carbon particle size remained the same even after increasing the milling time. Qanytah et al (2020) added that a longer milling process reduces the sample crystallinity, producing an amorphous sample, as displayed in Fig. 5.…”
Section: Morphological and Porosity Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, 93 full-text articles were reviewed, out of which 44 studies were eligible for the qualitative analysis according to the established inclusion criteria. The 44 papers were composed of articles containing the physicochemical and adsorption properties of ACs from the three selected biomass sources with the respective distributions: coconut shell [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], bamboo [16,[23][24][25][26][27][28][29][30][31][32][33][34] and rice husk [35][36][37][38][39][40][41][42][43][44][45][46][47][48]. The analyses were divided into two categories: (a) synthesis conditions affecting the differences in physicochemical properties of ACs and (b) effects of physicochemical properties onto MB adsorption performance.…”
Section: Resultsmentioning
confidence: 99%